Influence of feeding the developed fodder additive on the development of internal organs of egg cross chicken - N. A. Yurina; A. B. Vlasov; A. A. Danilova; L. N. Skvortsova (Новые технологии, 2018)
The article describes the results of studies of the effect of a natural feed supplement based on the bottom sediments of the Khan Lake of the Krasnodar Territory on the development of internal organs of young laying hens. It has been experimentally confirmed that there are no pathologies in the structure of internal organs of the poultry of experimental groups when feeding the studied fodder additive.